Bathymetric analysis using multifrequency multibeam echosounder - Khomsin; Danar Guruh Pratomo; Aditya Nugraha; Muhammad Arif Zulkarnaen (Geodesy and Cartography)
Making a nautical chart for safe navigation is a bathymetric survey’s primary goal. Multifrequency MBES have been developed over the last few decades, and their introduction has dramatically improved the efficiency, accuracy, and spatial resolution of coastal and ocean mapping. The goal of multifrequency MBES is to increase the subsurface’s detection resolution. To obtain an accurate picture of the seabed, the user can lessen the impact of this subsidence by running surveys in three different modes at once. With the help of multifrequency MBES, this study will analyze bathymetry in shallow coastal waters. The digital bathymetric model’s (DBM) frequencies are remarkably close. The depth value of the study site ranges from –20 m to–70 m with reference to lowest water surface (LWS) based on the produced DBM. Generally, the difference between 100 kHz, 200 kHz, and 400 kHz is as small as 0–30 cm, and a small part is 30–60 cm. The volume between frequencies for an area of 1 ha is between 90 m3 to 440 m3. If the thickness of the dredged sediment is 1 m, then the difference in volume between frequencies is less than 5%. The bathymetry difference between 100 kHz and 400 kHz frequencies to –10 cm is dominated by the region of 0 cm. Dredging volume inter frequency ranges from 0.042 m3/m2 to 0.068 m3/m2.